Peroral endoscopic myotomy as a treatment for Killian–Jamieson diverticulum (KJ-POEM) - Assefa, Redeat Libanos; Bejjani, Michael; Mehta, Amit; Shrigiriwar, Apurva; Fayyaz, Farimah; Shimamura, Yuto; Inoue, Haruhiro; Mandarino, Francesco Vito; Azzolini, Francesco; Bowers, Steven P; Li, Zhen; Robles-Medranda, Carlos; Arevalo, Martha; Dhir, Vinay; Andrisani, Gianluca; Tantau, Alina; Lajin, Michael; Sampath, Kartik; Khashab, Mouen A. (Endoscopy International Open, 2024)
Background and study aims Killian-Jamieson diverticulum (KJD) is a rare type of esophageal diverticulum that occurs in a specific area called the Killian-Jamieson space. Although surgery has been the conventional treatment for symptomatic KJD, minimally invasive endoscopic techniques, particularly Killian-Jamieson per-oral endoscopic myotomy (KJ-POEM), have emerged as an alternative. The aim of the study was to evaluate the effectiveness and safety of KJ-POEM in treating KJD.Patients and methods This was an international, multicenter, retrospective study that included patients who underwent KJ-POEM for symptomatic KJD from October 16, 2018 to April 12,2023. The primary outcome was clinical success, defined as complete or near-complete resolution of symptoms (i.e., post-procedure Kothari-Haber Score ≤ 2).  Secondary outcomes were technical success (defined as successful completion of all procedural steps), rate and severity of adverse events (AEs), total procedure duration, and symptom recurrence during follow-up.Results A total of 13 patients (mean age 65.23 years, 6 female) with KJD and a mean pre-procedure Kothari-Haber Score of 6 (standard deviation [SD] 2.16) underwent KJ-POEM across 10 participating centers. Clinical success and technical success were achieved in all cases (100%) with a mean post-procedure Kothari-Haber Score of 0.91 (SD 0.99). There were no AEs and no cases of injury to the recurrent laryngeal nerve. Mean length of hospital stay was 1.09 days (SD 0.74). Mean follow-up time was 9.41 months (SD 10.07) post-procedure. There was no post-procedure symptom recurrence any patient.Conclusions KJ-POEM is a safe and effective alternative treatment for symptomatic KJD with excellent short/mid-term outcomes.
Keywords: Endoscopy Upper GI Tract